Construction of a Comprehensive Competency Evaluation Index System for Master of Nursing Specialist Postgraduates (Contemporary Education and Teaching Research, 2025)
This study aimed to construct a comprehensive competency evaluation index system for Master of Nursing Specialists (MNS) postgraduates to support standardized assessment of training outcomes. A preliminary set of indicators was developed through literature analysis, semi-structured interviews, and group discussions, followed by a two-round Delphi survey to refine the indicators. The analytic hierarchy process was then applied to determine the weight of each indicator. Expert response rates reached 96% and 100% in the two rounds, with authority coefficients of 0.919 and 0.927, respectively. Kendall’s W values were 0.171 and 0.289 (both P